PERBANDINGAN EFEKTIVITAS RIVAROXABAN DAN WARFARIN DALAM MENGATASI KEJADIAN EMBOLI PADA PASIEN DENGAN ATRIAL FIBRILASI - Filipo David Tamara (Jurnal Ners, 2023)
Atrial Fibrillation (AF) is one of the most common types of cardiac arrhythmias caused by abnormal electrical activity in the heart's atria. A study conducted in Indonesia on the urban population in Jakarta obtained an AF incidence rate of 0.2% with a male to female ratio of 3:2. Oral anticoagulant therapy is the standard therapy for AF to prevent stroke and systemic embolism. The most widely used oral anticoagulants are Vitamin K Antagonist (VKA) such as Warfarin and Direct Oral Anticoagulants such as Rivaroxaban. This literature author conducted to compare the effectiveness. Warfarin and Rivaroxaban in dealing with embolic events in AF patients to find out which type of anticoagulant should be used. The literature sources used were Pubmed, Google Scholar, Medline, Ebsco, Hindawi, Science Direct and Cochrane. Anticoagulants have been used to prevent embolic disease in AF patients and the drug classes used are DOAC and VKA. Based on a literature search it was found that Rivaroxaban can reduce the risk of stroke and systemic embolism as well as major bleeding events compared to Warfarin. Rivaroxaban has been shown to have superior effectiveness compared to warfarin and can be used as an alternative drug in treating embolic events in AF patients.